2020
DOI: 10.1039/d0cc06031c
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-principle for two-stage photodynamic therapy: hypoxia triggered release of singlet oxygen

Abstract: Singlet oxygen, which is stored in the form of an endoperoxide, released under hypoxic conditions typically prevalent in most tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Two stage PDT can overcome the issues of light attenuation and oxygen deficiency in tumors. Reproduced from (Ayan et al, 2020) (published by The Royal Society of Chemistry) with permission from the Royal Society of Chemistry. FIGURE 8 | Fractional PDT.…”
Section: Low Ph and High Intracellular Glutathione (Gsh) Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Two stage PDT can overcome the issues of light attenuation and oxygen deficiency in tumors. Reproduced from (Ayan et al, 2020) (published by The Royal Society of Chemistry) with permission from the Royal Society of Chemistry. FIGURE 8 | Fractional PDT.…”
Section: Low Ph and High Intracellular Glutathione (Gsh) Concentrationmentioning
confidence: 99%
“…It remains in an “OFF” state (inactivated PS), unless activated by chemical/biochemical parameters into the “ON” state (activated PS) in the tumor region. Examples of such parameters are overexpressed enzymes/proteins ( Yuan et al, 2014 ; Digby et al, 2020 ) and higher intracellular glutathione concentration in cancer cells ( Cakmak et al, 2011 ; Turan et al, 2014 ; Erbas-Cakmak et al, 2015 ; Kolemen et al, 2015 ); hydrogen peroxide ( Wang Y. et al, 2021 ); low pH of the environment ( Tian et al, 2015 ); hypoxia ( Ayan et al, 2020 ) and cathepsin B ( Kim et al, 2014 ). The working principle of this switch generally involves cleavage of an intramolecular linker, which is connected to the PS as a quenching moiety.…”
Section: Novel Approaches To Improve Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Problems such as lack of selectivity, poor water-solubility, possible toxic effects on healthy tissues, skin photosensitivity that is associated with certain PSs may prevent the clinical applications of various PDT approaches. Many research groups have undertaken the task to overcome such issues and several promising targeted approaches have been reported over the last years ( Turan et al, 2016 ; Karaman et al, 2019 ; Ayan et al, 2020 ). Novel innovative strategies aim to increase the delivery of PSs to tumor tissues, to augment specificity and to increase efficiency ( Bugaj, 2011 ).…”
Section: Clinical Applications Of Photodynamic Therapy In Cancermentioning
confidence: 99%
“…Therefore, cancer cells require a robust antioxidant system in order to be able to survive. It was reported that the cytotoxic effects of PDT are enhanced when antioxidant enzymes or glutathione synthesis mechanisms are targeted during PDT ( Ayan et al, 2020 ). It was demonstrated that l -buthionine sulfoximine, which is a glutathione synthesis inhibitor, boosts PDT effects.…”
Section: Clinical Applications Of Photodynamic Therapy In Cancermentioning
confidence: 99%